2019
DOI: 10.1108/mmms-03-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal radiation on engine oil nanofluid flow over a permeable wedge under convective heating

Abstract: Purpose The purpose of this paper is to examine the magneto hydrodynamic flow and heat transfer of nanofluids over a permeable wedge based on engine oil which is under the effects of thermal radiation and convective heating. Design/methodology/approach The equations governing the flow are transformed into differential equations by applying similarity transformations. Keller box method is used to bring out the numerical solution. Findings The discovery interprets that temperature as well as the velocity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Graphs are used to show the velocity and temperature profiles of the hybrid nanofluids that are affected by the parameters, while tables are used to show the skin friction and Nusselt number that are impacted by the parameters. Table 2 shows the direct comparison in the term of skin friction coefficient that obtained in the present study with the numerical results reported by Watanabe [47], Khan et al, [33], Yih [48], Mabood et al, [49] and Kotha et al, [41] to validate the validity and accuracy of the current analysis. The reported findings are in food accordance with reported in previous study.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Graphs are used to show the velocity and temperature profiles of the hybrid nanofluids that are affected by the parameters, while tables are used to show the skin friction and Nusselt number that are impacted by the parameters. Table 2 shows the direct comparison in the term of skin friction coefficient that obtained in the present study with the numerical results reported by Watanabe [47], Khan et al, [33], Yih [48], Mabood et al, [49] and Kotha et al, [41] to validate the validity and accuracy of the current analysis. The reported findings are in food accordance with reported in previous study.…”
Section: Resultssupporting
confidence: 75%
“…The base fluid is considered to be water with hybrid nanoparticles of silver (Ag) and magnesium oxide (MgO) that are in thermal equilibrium. Assuming a two-dimensional and steady flow in the laminar boundary layer, the governing equations are given as follows [41]:…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gangadhar et al [19] examined the insecure progression of free convective boundary layers of nanofluids on extended surfaces. Gangadhar et al [20] considered the impact of warm radiation on the progression of nanofluids from oil through penetrable wedges.…”
Section: Introductionmentioning
confidence: 99%
“…Dogonchi et al (2018aDogonchi et al ( , 2018b investigated the free convection of copper nanoparticle through a triangular cavity. Magnetohydrodynamic flow over a wedge has been examined by Kotha et al (2019). They obtained that temperature is greater in case of Ag-engine oil than Cu-engine oil nanoliquid.…”
Section: Introductionmentioning
confidence: 99%